2007
DOI: 10.1177/1076029608322550
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Immunogenic Potential of Membrane Filtered Bovine Thrombin Preparations for Hemostatic Application

Abstract: on the reduction of trace contaminants such as the bovine factor Va/Va light chain fragments to an undetectable level in thrombin 4B. In order to compare the relative immunogenic potential, bovine crude thrombin and its purified versions, 4A and 4B preparations, were administered intravenously to individual groups of rabbits on day 0 and day 21 using standard immunologic protocols. Antiserum was drawn from each rabbit on day 30 and the pooled antisera were purified to obtain the IgGs using protein G affinity c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…The data from our initial study had shown that preimmune IgG obtained from the rabbits did not demonstrate any recognition of epitopes in bovine crude thrombin, thrombin 4A, thrombin 4B, and factor Va light chain. 27 The results from this study clearly demonstrated that factor V/Va contaminants in bovine thrombin preparations do not appear to generate an immune response in a naive rabbit model even after repeated exposure. Therefore, this observation points to a possibility that the reported presence of anti-bovine factor Va antibodies in some patients exposed to bovine crude thrombin may be caused by an immune response to the preexisting bovine immunogens in these patients.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…The data from our initial study had shown that preimmune IgG obtained from the rabbits did not demonstrate any recognition of epitopes in bovine crude thrombin, thrombin 4A, thrombin 4B, and factor Va light chain. 27 The results from this study clearly demonstrated that factor V/Va contaminants in bovine thrombin preparations do not appear to generate an immune response in a naive rabbit model even after repeated exposure. Therefore, this observation points to a possibility that the reported presence of anti-bovine factor Va antibodies in some patients exposed to bovine crude thrombin may be caused by an immune response to the preexisting bovine immunogens in these patients.…”
Section: Discussionmentioning
confidence: 60%
“…27 This finding in rabbits is inconsistent with the data obtained from human patients following exposure to topical bovine thrombin during surgery. [4][5][6][7][8] It was thought that the development of anti-bovine factor Va antibodies might have slower onset as compared to antithrombin IgGs in rabbit and therefore, a longer immunization time may be needed to generate anti-bovine factor Va antibodies in rabbits than in humans.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations